Social Cohesion of the Armenian Diaspora in Russia: Theory and Practice of Measurement - Galina I. Osadchaya; Egor Yu. Kireev; Marina L. Vartanova; Maria V. Roslavtseva (Социологическая наука и социальная практика, 2022)
The social cohesion of the Armenian Diaspora in Russia is the most important condition for ensuring its well-being, vitality, stability of daily life, creating conditions for the realization of socioeconomic potential in the interests of Russia and Armenia. However, despite the attention to the study of various aspects of its functioning as an ethnocultural and ethnopolitical phenomenon, this problem has remained outside the Russian scientific discourse. The purpose of the article is to show the mechanisms of formation of cohesion, social ties, altruistic behavior, to reveal the forms of exchange, interaction, cooperation in the interests of meeting the needs of members of the Armenian Diaspora as a way of capitalizing trust based on similarity of interests and awareness of oneself as a special ethnic group. The methodology of studying the social cohesion of the Armenian Diaspora in Russia is determined by the specifics of the subject under study, the author’s research approach to measuring this phenomenon, the purpose of the study, as well as the theoretical constructs of social cohesion that allow us to articulate the results more clearly. The methodological strategy includes a questionnaire survey of 1,273 members of the Armenian Diaspora in the Moscow agglomeration, Krasnodar and Stavropol Territories. The article proposes a multidimensional model for assessing the social cohesion of the Armenian Diaspora in Russia, representing a system of criteria characterizing its essential features, which includes subjective representations and behavioral aspects of mutual assistance and interaction of diaspora members. Based on the analysis of empirical data on the social cohesion of the Armenian Diaspora in Russia, four groups are identified: the central one is the most numerous, representing a cohesive core, the peripheral one is a group of the alienated, a group of undecided in assessing the degree of cohesion of the Armenian diaspora and marginals. Measuring the cohesion of the diaspora based on the material of quantitative empirical research is difficult and has limitations. However, it allows avoiding the subjectivity of the conclusions of studies conducted on small samples, clarifying not only the state, but also the causes and consequences, which is productive for assessing the social cohesion of the Armenian Diaspora.